Pemilahan Sampah dengan Manual Pilah Sampah untuk Mendukung Perkembangan Bank Sampah Berbek Mandiri di Desa Berbek Kecamatan Waru Kabupaten Sidoarjo Propinsi Jawa Timur - SRI WIDYASTUTI; Setyo Purwoto; Pungut (Jurnal Penamas Adi Buana, 2021)
The problem that arises in Berbek Village, Waru District, Sidoarjo Regency is that the community has not carried out waste management properly. Garbage is simply thrown into a Temporary Waste Disposal Site (TPS) or burned even though there is a Trash Bank. The purpose of implementing Community Service is training and outreach to the people of Berbek village to be able to sort waste, recognize the types of waste that have economic value so that they can be cached at the Waste Bank and the residue that can enter TPST / TPA. Service implementation methods: socialization, training and hands-on practice. The results obtained by the community members carry out waste sorting and deposit dry waste to the Trash Bank.